2021
DOI: 10.1136/bmjoq-2021-001449
|View full text |Cite
|
Sign up to set email alerts
|

Development of a framework of intervention strategies for point of care quality improvement at different levels of healthcare delivery system in India: initial lessons

Abstract: BackgroundInadequate quality of care has been identified as one of the most significant challenges to achieving universal health coverage in low-income and middle-income countries. To address this WHO-SEARO, the point of care quality improvement (POCQI) method has been developed. This paper describes developing a dynamic framework for the implementation of POCQI across India from 2015 to 2020.MethodsA total of 10 intervention strategies were designed as per the needs of the local health settings. These strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“… 39 Moreover, the strategy of POCQI implementation also successfully in improving quality of care in 131 facilities in India. 40 PHCs and hospitals in the district have limited resources. PHC and public hospitals are under the responsibility of the DHO in the local health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 Moreover, the strategy of POCQI implementation also successfully in improving quality of care in 131 facilities in India. 40 PHCs and hospitals in the district have limited resources. PHC and public hospitals are under the responsibility of the DHO in the local health system.…”
Section: Discussionmentioning
confidence: 99%
“…POCQI implementation encourages community decision making, health workers and national health system policies. 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent regional study by Patodia J et al showed that implementation of WHO POCQI resulted in overall reduction of hyperthermia from 82% to 45%. 12 POQCI is cost effective approach that can reduce neonatal intensive care unit (NICU) admissions while in a developing country like Pakistan with resource limitations, prevention of hypothermia can potentially reduce overall burden of morbidity and mortality. 19,20 Our study had some limitations as well.…”
Section: Discussionmentioning
confidence: 99%
“…NMU was one of the centers in Pakistan where POCQI wa implemented. [10][11][12] The main purpose was to introduce four components of early essential newborn care to all the newborn babies to reduce neonatal mortality rate and improve care to mother and baby. Prior to this initiative by UNICEF, there was no set protocol for immediate care of newborn babies in labor room NMU and data was not collected regarding neonatal morbidity and mortality resulting from neonatal hypothermia, hypoglycemia and infection.…”
Section: Introductionmentioning
confidence: 99%